IMPLEMENTASI MODEL PEMBELAJARAN PROBING PROMPTING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V MIN SIBUHUAN - Nur Saniah Nasution; Lailan Aprina Siregar; Rizki Hamdan Saputra (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The aim of this research is to determine (1) the learning motivation of fifth grade students at MIN Sibuhuan. (2) Implementation of the probing prompting learning model to increase the learning motivation of class V MIN Sibuhuan students. The type of research used is Classroom Action Research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. This research was carried out in class V of MIN Sibuhuan. The data sources in this research were divided into two, namely (1) primary data, namely students of class V MIN Sibuhuan (2) secondary data, namely class V teachers of MIN Sibuhuan. Data collection techniques in this research were obtained through observation and documentation. The data analysis technique in this research is a qualitative data analysis technique. Based on the research results, it can be concluded that (1) The learning motivation of class V MIN Sibuhuan students pre-cycle is still low, namely 4 students or 12.50% have "very good" learning motivation, 8 students or 25.00% have "good" learning motivation, 15 students or 46.88% had "fairly good" learning motivation, 5 students or 15.63% had "poor" learning motivation, no students had "very poor" motivation. (2) The implementation of the probing prompting learning model to increase the learning motivation of class V students of MIN Sibuhuan cycle I has begun to increase, namely 6 students or 28.13% have "very good" learning motivation, 15 students or 46.88% have "good" learning motivation. , 8 students or 25.00% had "quite good" learning motivation, there were no students with "poor" learning motivation, no students had "very poor" motivation. In cycle II, the learning motivation of class V MIN Sibuhuan students had increased, namely 21 students or 65.63% had "very good" learning motivation, 10 students or 31.25% had "good" learning motivation, 1 student or 3.13% had "good" learning motivation. "fairly good", there are no students with "poor" motivation to learn, there are no students with "very poor" motivation.